2021
DOI: 10.1016/j.heliyon.2021.e06687
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors of stigma and relationship to healthcare services among adolescents living with HIV/AIDS in Kano state, Nigeria

Abstract: Background Stigma associated with HIV shapes all aspect of prevention and treatment, yet there are limited data on how HIV-infected adolescents are affected by stigma. Stigma increases risk of psychological problems among HIV-infected individuals which can affect access to treatment and social support services. This study aimed at identifying psychosocial factors of stigma and relationship to healthcare services among adolescents on antiretroviral therapy (ART) in Gwale Local Government Area (LGA)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…This means that the greater the social support provided to PLWHA, the better their quality of life. This finding is also supported by other studies that showed the effect of social support on quality of life [13][14][15][16].…”
Section: Discussionsupporting
confidence: 89%
“…This means that the greater the social support provided to PLWHA, the better their quality of life. This finding is also supported by other studies that showed the effect of social support on quality of life [13][14][15][16].…”
Section: Discussionsupporting
confidence: 89%
“…In Benue State, fear of stigma and discrimination has a significant influence on the health-seeking behaviour of PLHIV and this is consistent with findings from previous studies [33][34][35][36]. Due to this fear, many PLHIV travel long distances far from where they reside to receive ART, in addition, a lack of means of reaching them such as via telephone and ill-defined physical address, results in delay in enrolment in EAC.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies have found that AYA living with HIV can face negative consequences due to others finding out about their status including that of being socially rejected and isolated. [59][60][61] Both perceived and experienced social rejection are common occurrences that AYA living with HIV face. 59,62 Perceived social rejection itself perpetuates AYA living with HIV being advised to and actively choosing not to disclose their status.…”
Section: Discussionmentioning
confidence: 99%